Role Of Microalgal Organic Matterderived Biocoating Towards Cell Deposition In Natural Biofilm Formation - Lim, Siew Li (Universiti Sains Malaysia, 2022)
Biofilm-based algal cultivation is gaining popularity as a viable platform for algal production, wastewater treatment and as a feedstock source for microalgae-based biorefinery initiatives. However, the interaction between cells and biocoatings are poorly understood. In this paper, the degree of adhesion Navicula incerta on commercial microporous polyvinylidene fluoride (PVDF) membrane strip surface before and after coating with AOM namely bounded extracellular polymeric substances (bEPS), the soluble extracellular polymeric substances (sEPS) and intracellular organic matter (IOM) extracted from Navicula sp. was studied. Furthermore, the polysaccharide, protein and hydrophobicity of the sEPS, bEPS and IOM of Navicula sp. on pristine and pre-treated PVDF membrane surfaces were investigated. The findings showed that microalgal cell adhesion had higher adhesion on coated membrane PVDF strips than pristine membranes. This was because EPS on the pre-coated membranes provided a gel-like network to form a strong biofilm adhesion to surfaces. It was found out that surfaces with higher hydrophobicity and surface roughness provided better cell adhesion and stronger biofilm formation. The productivity of sEPS polysaccharide was higher than the productivity of sEPS protein. Also, the bEPS had higher productivity of polysaccharide than of protein. However, the protein in IOM exhibited practically consistent concentration on four different coated membrane strips. Carbohydrates and proteins are the required elements for the biofilm formation. Surface wettability of EPS also influences cell attachment.